2020
DOI: 10.1097/mnm.0000000000001267
|View full text |Cite
|
Sign up to set email alerts
|

123I-Ioflupane dopamine transporter imaging (DaTSCAN) appearances in relation to emotional responsiveness, impulsivity and olfaction in suspected Parkinsonian syndrome

Abstract: Objective The aim of our study was to ascertain relationships between DaTSCAN, olfactory loss, behavioural and subjective measurements of impulsivity and emotional responsiveness in patients with clinically suspected Parkinsonian syndrome (PS). Methods A prospective study of 20 drug-naive patients with parkinsonism, underwent the University of Pennsylvania Smell Identification Test, impulsivity measurements and mood-state-questionnaires before visual an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Several DAT imaging studies revealed an association between decreased striatal DAT availability and non-motor symptoms in PD including anxiety [ 251 ], depression [ 252 , 253 , 254 ], apathy [ 255 ], impulsivity [ 239 , 256 ], fatigue, constipation [ 240 ], hyposmia [ 257 , 258 , 259 , 260 ], autonomic symptoms [ 261 , 262 , 263 , 264 , 265 , 266 ], sleep disturbances, daytime sleepiness [ 267 ], body weight loss [ 268 ] and visual hallucinations [ 241 ], in support of a partial dopaminergic pathogenesis [ 269 ] ( Table 1 ). In a recent study using data from sequential DAT-SPECT imaging in 344 PD patients from the PPMI dataset, Liu and colleagues demonstrated a significant association between DAT binding both at baseline and at follow-up scans and several baseline non-motor symptoms, with RBD showing the strongest association with concurrent and future DAT binding [ 270 ].…”
Section: Dat Imaging As Predictive Biomarker: Non-motor Measuresmentioning
confidence: 99%
“…Several DAT imaging studies revealed an association between decreased striatal DAT availability and non-motor symptoms in PD including anxiety [ 251 ], depression [ 252 , 253 , 254 ], apathy [ 255 ], impulsivity [ 239 , 256 ], fatigue, constipation [ 240 ], hyposmia [ 257 , 258 , 259 , 260 ], autonomic symptoms [ 261 , 262 , 263 , 264 , 265 , 266 ], sleep disturbances, daytime sleepiness [ 267 ], body weight loss [ 268 ] and visual hallucinations [ 241 ], in support of a partial dopaminergic pathogenesis [ 269 ] ( Table 1 ). In a recent study using data from sequential DAT-SPECT imaging in 344 PD patients from the PPMI dataset, Liu and colleagues demonstrated a significant association between DAT binding both at baseline and at follow-up scans and several baseline non-motor symptoms, with RBD showing the strongest association with concurrent and future DAT binding [ 270 ].…”
Section: Dat Imaging As Predictive Biomarker: Non-motor Measuresmentioning
confidence: 99%
“…DATs are located densely in the striata, which consists of the caudate nucleus and putamen. DaTSCAN can be conducted in vivo using single-photon emission computed tomography (SPECT) imaging to visualize and assess dopaminergic activity within this area [5,6]. This can assist in diagnosis when the clinical evaluation is inconclusive [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, between four to fifteen percent of patients with clinical suspicion of idiopathic Parkinson’s disease (IPD) and 10% of patients with corticobasal degeneration, both of which are types of neurodegenerative Parkinsonian syndromes, demonstrate a normal uptake of DaTSCAN [10,11]. This has led to the use of the acronym SWEDD, scans without evidence of dopaminergic deficit, to classify these patients [5].…”
Section: Introductionmentioning
confidence: 99%